Repertoires of knowledge practices: social movements in times of crisis. Issue 4 (13th November 2017) - della Porta, Donatella; Pavan, Elena
Abstract : Purpose: Starting from the assumption that knowledge becomes all the more important for movements in times of crisis, as old structures are challenged and new ones envisaged and proved feasible, the purpose of this paper is to suggest ways to expand the toolkit of social movement studies in order to empirically address knowledge practices as a meaningful part of contemporary progressive activism. Design/methodology/approach: The authors start by arguing that, in their effort to pursue or resist social and political changes, contemporary progressive social movements form collective spaces of knowledge production that are true laboratories for innovation. For this reason, the authors begin by making a case for accounting more explicitly for knowledge production within social movement studies - not as a substitution for but, rather, as a necessary complement to current cultural approaches. Building on extant literature on the nexus between movements and knowledge, the authors then outline the peculiarities of movement knowledge. Findings: On these bases, the authors outline the core components of what the authors call repertoires of knowledge practices - that is, the set of practices that foster the coordination of disconnected, local, and highly personal experiences and rationalities within a shared cognitive system able to provide movements and their supporters with a common orientation for making claims and acting collectively to produce social, political, and cultural changes. Originality/value: The authors conclude by identifying some promising avenues of research to further develop the understanding of movement practices of knowledge production and transmission.